Hak Fungsi Reproduksi Bagi Warga Binaan Pemasyarakatan Perempuan Di Indonesia - Betesda, Betesda; Tumanggor, M.S; Setyowati, Dwi Andayani (JURNAL HUKUM PELITA, 2025)
Provisions regarding the fulfillment of rights for inmates have been regulated both nationally and internationally, especially for female inmates. A country's policy must be a strong foundation for fulfilling the rights of female inmates, especially in reproductive functions and improving their health in correctional institutions. This writing uses a doctrinal research method, namely based on doctrine, regulations, principles, norms or values ​​and through literature studies with identification of legal sources by analyzing the legal sources. This study uses a comparative law approach to solve related problems. Comparative law aims to compare the laws of a country, the laws of a time and court decisions